FlyBase 2.0: the next generation. Issue Volume 47:Issue D1(2019) (26th October 2018) - Thurmond, Jim; Goodman, Joshua L; Strelets, Victor B; Attrill, Helen; Gramates, L Sian; Marygold, Steven J; Matthews, Beverley B; Millburn, Gillian; Antonazzo, Giulia; Trovisco, Vitor; Kaufman, Thomas C; Calvi, Brian R; et al.
Abstract: FlyBase (flybase.org ) is a knowledge base that supports the community of researchers that use the fruit fly, Drosophila melanogaster, as a model organism. The FlyBase team curates and organizes a diverse array of genetic, molecular, genomic, and developmental information about Drosophila . At the beginning of 2018, 'FlyBase 2.0' was released with a significantly improved user interface and new tools. Among these important changes are a new organization of search results into interactive lists or tables (hitlists), enhanced reference lists, and new protein domain graphics. An important new data class called 'experimental tools' consolidates information on useful fly strains and other resources related to a specific gene, which significantly enhances the ability of the Drosophila researcher to design and carry out experiments. With the release of FlyBase 2.0, there has also been a restructuring of backend architecture and a continued development of application programming interfaces (APIs) for programmatic access to FlyBase data. In this review, we describe these major new features and functionalities of the FlyBase 2.0 site and how they support the use of Drosophila as a model organism for biological discovery and translational research.